Principles of Business Updated, Precision Exams Edition, 9th Edition - Les Dlabay (Cengage Learning, 2018)
PRINCIPLES OF BUSINESS, Updated Precision Exams Ninth Edition, provides complete instruction in business concepts and skills students need in today's competitive environment. This market-leading introductory business text offers extensive coverage in major business concepts, such as finance, marketing, operations, and management. Students gain valuable information and skills for the workplace, as well as preparation for success in competitive events, such as DECA, FBLA, and BPA. This edition correlates 100% to the Precision Exams Business Concepts Exam. MindTap for Principles of Business Updated, Precision Exams Edition, 9th edition is the digital learning solution that helps teachers engage and transform today's students into critical thinkers. Through paths of dynamic assignments and applications that you can personalize, real-time course analytics and an accessible reader, MindTap helps you turn cookie cutter into cutting edge, apathy into engagement, and memorizers into higher-level thinkers. MindTap for this course includes the full, interactive eBook as well as auto-graded reading activities throughout the eBook for each lesson as well as student tools like flashcards, practice quizzes, and auto-graded homework and tests.